Finalización submarina de un pozo de reinyección de corte en la cuenca de santos (2022)
When there is a hydrocarbon producing well, cuttings are generated due to the work generated by the drill bit against the rock, these cuttings become waste from the process and are sent to different holders for disposal. Since the '70s, drilling engineering must comply with environmental standards for waste management.